Different Imaging Modalities for Evaluating Emphysematous Pyelonephritis (EPN); a Life Threatening Urological Emergency – A case report - Afrin, Rawnak; Mostofa, ABM Golam; Biswas, Shankar Kumar; Hossain, Sadia; Hossain, Sanowar (Bangladesh Journal of Nuclear Medicine, 2018)
Emphysematous pyelonephritis (EPN) is a severe necrotizing infection of the renal parenchyma; it causes gas formation within the collecting system, renal parenchyma, and/or perirenal tissues. In this reported case, a female patient of 40 years was admitted in a tertiary hospital with history of severe left flank pain, lower abdominal pain, fever, vomiting and scanty micturition for three days. Ultrasonogram showed-normal right kidney but left renal bed reveals extensive air obscuring visualization of left kidney with probe tenderness in left flank. Contrast CT scan of KUB shows larger left kidney with extensive air (CT number = -1000 HU) within the renal parenchyma, collecting systems and perinephric space. This case was diagnosed as EPN. After conservative treatment patient was improved significantly. Bangladesh J. Nuclear Med. 20(1): 63-66, January 2017